2006
DOI: 10.1128/jvi.80.8.3923-3934.2006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Production and In Vitro Behavior of CD27-Defined B-Cell Subsets: Persistent Hepatitis C Virus Infection Changes the Rules

Abstract: ؉ B cells do not expand but rapidly differentiate to secrete Ig and then undergo apoptosis. We propose that their enhanced sensitivity to BCR-independent noncognate T-cell help maintains a constant level of nonspecific serum antibodies and ASC and serves as a backup mechanism of feedback inhibition to prevent exaggerated B-cell responses that could be the cause of significant immunopathology.Exploration of the conditions that stimulate and modulate B-cell proliferation and differentiation is critical to both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
48
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 81 publications
14
48
1
3
Order By: Relevance
“…Somewhat unexpectedly, chronic B-cell activation in chronic hepatitis C does not result in expansion of the memory B-cell pool in cohorts of mostly non-cirrhotic individuals [7][8][9]. Possible reasons cited for the lack of peripheral memory B-cell expansion include increased plasma cell differentiation [8], increased activation-induced B-cell apoptosis [8], and intrahepatic compartmentalization [10]. Among these explanations, activation-induced apoptosis has been contradicted by more recent data suggesting that B-cells in HCV-infected individuals are relatively resistant to apoptosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat unexpectedly, chronic B-cell activation in chronic hepatitis C does not result in expansion of the memory B-cell pool in cohorts of mostly non-cirrhotic individuals [7][8][9]. Possible reasons cited for the lack of peripheral memory B-cell expansion include increased plasma cell differentiation [8], increased activation-induced B-cell apoptosis [8], and intrahepatic compartmentalization [10]. Among these explanations, activation-induced apoptosis has been contradicted by more recent data suggesting that B-cells in HCV-infected individuals are relatively resistant to apoptosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C infection is characterized by profound hyperglobulinemia consisting of nonvirus-specific antibodies [3,4] produced by oligoclonally-activated B-cells [5,6]. Somewhat unexpectedly, chronic B-cell activation in chronic hepatitis C does not result in expansion of the memory B-cell pool in cohorts of mostly non-cirrhotic individuals [7][8][9]. Possible reasons cited for the lack of peripheral memory B-cell expansion include increased plasma cell differentiation [8], increased activation-induced B-cell apoptosis [8], and intrahepatic compartmentalization [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cacoub and colleagues 4 found reductions in the percentage of naïve B cells in MC patients compared with normal controls and, as in our study, the size of the naïve B cell subset was restored after rituximab therapy. Racanelli et al 5 and Oliviero et al 6 found no changes in B cell frequency, whereas Ni et al 7 observed an increase, but only in patients suffering from severe liver disease. In the figure that Sansonno et al included in their letter, it is unusual that the patients were categorized based on B cell percentages of <5%, 6%-10%, 11%-20%, and >20%.…”
Section: Reply: B-cell Frequency In Hcv-related Mixed Cryoglobulinemiamentioning
confidence: 97%
“…Наши ре-зультаты согласуются с данными литературы, свидетельствующими, что количество общих В-лимфоцитов (CD19 + ) в крови больных ХВГС не изменяется [16,19]. Вместе с тем, некоторые авторы отмечают снижение уровня CD27 + В-лимфоцитов при ХВГС, что может объясняться несколькими причинами.…”
Section: результаты и обсуждениеunclassified